Konsep Wajilat Qulubuhum dalam Tafsir Ruh Al-Ma’ani - Hardiyansyah Pakaya; Ilyas Daud; Kamaruddin Mustamin (AL-AQWAM: Jurnal Studi Al-Quran dan Tafsir, 2022)
The main study discussed in this research is the concept of wajilat qulu>buhum in the interpretation of Ru>h} al-Ma’a>ni Mah}mu>d al-Alu>sy. There are three aspects that want to be answered in this paper, namely: first, the concept of wajilat qulu>buhum in language analysis, second, the concept of wajilat qulu>buhum in the interpretation of Ru>h} al-Ma’a>ni and the third, is to articulate this interpretation and then be faced with the current phenomenon. In this study, the author uses a type of qualitative research that focuses on literature research using a Sufi (Sufism) approach. The results of this research show that the concept of wajilat qulu>buhum according to al-Alu>sy in QS al-Anfa>l/8: 2. Namely: that, the measure referred to as the absoluteness of perfect faith, then the judgment is not correct, then proceeds to the inaccuracy of the measure of faith, then no one knows, if it returns to the knowledge of the measure of faith, on the one hand it is not the same. With the previous rejection, faith, the perfect believer is the one whose heart is sincerely faithful. I am amazed, because i am proud of his majesty and for fear of him the most great, as mentioned in his words: “The most holy and all-high he (with the remembrance of God’s heart to be calm) does not contradict the fear of the previous verse with this verse. Because both, are forms of tranquility of heart, spaciousness of the chest, which is filled with science and belief, then united with fear”. In many ways in this life, we often hear or even meet with the so-called principle of causality (the principle of causality) for example: when the absence of light, means to indicate darkness, here that the absence of light results in darkness. This principle is inconsistent with the heart. If heart is given, then taste is inhern. Interestingly, by Mah}mu>d al-Alu>sy in interpreting this verse, that when we have reached the point of faith, then only by saying his name alone, our hearts will tremble.